The Influence of Visitor Engagement and Memorable Tourism Experiences on Revisit Intentions: Mediated by Visitor Satisfaction (A Study on Tourist Attractions In Kutai Kartanegara Regency) - Syifa Munawwarah; Iskandar Iskandar; Nilam Anggar Sari (Universitas Hamzanwadi, 2026)
This study aims to investigate how visitor engagement and memorable tourism experiences influence the intention to return to a destination, with visitor satisfaction acting as a mediating variable. To conduct this analysis, a quantitative approach was utilized, employing purposive sampling techniques to gather data from 160 respondents who have previously visited tourist destinations in Kutai Kartanegara Regency. The data were analyzed using SmartPLS software version 4.1.1.6. The findings indicate that visitor engagement and the quality of tourism experiences significantly contribute to overall visitor satisfaction. In turn, heightened visitor engagement and satisfaction are key predictors of guests' intentions to revisit a destination. However, memorable tourism experiences do not directly affect the revisit intention, but rather through the mediation of visitor satisfaction. These findings confirm that emotional engagement and meaningful tourism experience are the main factors that shape tourist loyalty. Therefore, destination managers need to increase tourist participation and create immersive tourism experience to strengthen satisfaction and revisit intention.